2016
DOI: 10.1111/cea.12830
|View full text |Cite
|
Sign up to set email alerts
|

The epithelial barrier and immunoglobulin A system in allergy

Abstract: Airway and intestinal epithelial layers represent first-line physical barriers, playing a key role in mucosal immunity. Barrier dysfunction, characterized by alterations such as disruption of cell-cell apical junctions and aberrant epithelial responses, probably constitutes early and key events for chronic immune responses to environmental antigens in the skin and in the gut. For instance, barrier dysfunction drives Th2 responses in atopic disorders or eosinophilic esophagitis. Such epithelial impairment is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 279 publications
(256 reference statements)
1
30
0
3
Order By: Relevance
“…Forceps and brush biopsies have revealed that immunoglobulins (Immunoglobulin G4 and Immunoglobulin E) are increased in EoE tissues 21 . Although not studied specifically in EoE, Immunoglobulin A is a known mucosal exclusion antibody secreted on the gastrointestinal surface to protect the body from potential threats, such as bacteria and viruses 22 . Local reactions within diseased tissues may also involve either secretory or immune‐mediated Immunoglobulin A production as seen in celiac disease 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Forceps and brush biopsies have revealed that immunoglobulins (Immunoglobulin G4 and Immunoglobulin E) are increased in EoE tissues 21 . Although not studied specifically in EoE, Immunoglobulin A is a known mucosal exclusion antibody secreted on the gastrointestinal surface to protect the body from potential threats, such as bacteria and viruses 22 . Local reactions within diseased tissues may also involve either secretory or immune‐mediated Immunoglobulin A production as seen in celiac disease 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Innate lymphoid cells and mast cells (MCs), in particular, orchestrate the mucosal regulatory system to create a mutually beneficial environment for both the host and the microbiota 30 . Barrier dysfunction drives Th2 responses in food anaphylaxis, atopic disorders or eosinophilic esophagitis 31 . Our findings showed that LAB strains (Bc and Lp) with notable anti-allergic effect against ST sensitization greatly restored the intestinal epithelial barrier functions by improvement of gut epithelial integrity, suppression of MCs degranulation in lamina propria, and skewing of the immune response from a Th2 to a Th1 polarization in MLN.…”
Section: Discussionmentioning
confidence: 99%
“…Non-live OLB6378 administration could be safe and beneficial to VLBW infants. Moreover, the increase in humoral immunity through non-live OLB6378 administration to full-term infants might be useful in the prevention of infantile allergies [32]. Further studies on the effects of non-live OLB6378 administration on not only VLBW infants but also on full-term infants in the early postnatal period are warranted.…”
Section: Discussionmentioning
confidence: 99%